Critical success factors of ERP implementation at retail franchise company in Indonesia - Fitriati Akmila; Imam Nur Fadilah; Herlina Rahmawati Dewi (Journal of Contemporary Accounting, 2023)
As technology develops, many companies seek to innovate and implement technology, one of them is ERP to support their business processes. One of these companies is PT Sumber Alfaria Trijaya, Jember, Indonesia. Many factors were affected the quality of ERP implementation. One of them is known as the Critical Success Factor (CFS). This study aimed to describe implementation of ERP application and the Critical Success Factors during ERP deployment at PT Sumber Alfaria Trijaya (SAT), Indonesia. This study used qualitative method for gaining data and research analysis. Interviewed are done with the key users. The results of analysis showed that five critical factors that supported and influenced the ERP implementation in the company, namely; Management Commitment and Support, User Involvement, Communication, Hardware and Equipment, and Education and Training. Those five factors have significant impact on the successful of ERP implementation at retail franchise company in Indonesia. In conclusion, the implementation of TAF application improved the quality of accounting information system information for the company.